2010
DOI: 10.1016/j.ijpharm.2010.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial growth and intramniotic infection in a guinea pig model of chorioamnionitis using PAMAM dendrimers

Abstract: Dendrimers have emerged as topical microbicides to treat vaginal infections. This study explores the in-vitro, in-vivo antimicrobial activity of PAMAM dendrimers, and the associated mechanism. Interestingly, topical cervical application of 500 µg of generation-4 neutral dendrimer (G4-PAMAM-OH) showed potential to treat the Escherichia coli induced ascending uterine infection in guinea pig model of chorioamnionitis. Amniotic fluid collected from different gestational sacs of infected guinea pigs post treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 52 publications
1
101
0
Order By: Relevance
“…2) and previous reports (30). The broad-spectrum antibacterial activity and toxicity to eukaryotic cells imply that PAMAM-NH 2 may disrupt cells irrespective of their species, and it has been suggested that PAMAM-NH 2 may damage cells through nonspecific physical mechanisms rather than by targeting specific molecules (19). The G2.0 PAMAM-NH 2 dendrimer is a polycation that may replace the divalent ions binding to the polyanions present in the cell membrane.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…2) and previous reports (30). The broad-spectrum antibacterial activity and toxicity to eukaryotic cells imply that PAMAM-NH 2 may disrupt cells irrespective of their species, and it has been suggested that PAMAM-NH 2 may damage cells through nonspecific physical mechanisms rather than by targeting specific molecules (19). The G2.0 PAMAM-NH 2 dendrimer is a polycation that may replace the divalent ions binding to the polyanions present in the cell membrane.…”
Section: Discussionmentioning
confidence: 89%
“…Chemical modifications of PAMAM-NH 2 dendrimers were demonstrated to reduce their toxicities, but these modifications simultaneously reduced the antibacterial activities of the PAMAM-NH 2 dendrimers (11,16). To date, antibacterial research on PAMAM-NH 2 dendrimers has been limited to topical (17)(18)(19) and drug carrier applications (20)(21)(22). Insufficient data are available to determine whether PAMAM-NH 2 dendrimers could be used systemically as antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Many already are or may soon become useful tools with applications in various fields of biomedical science. Dendrimers could play a role as efficient drug, nucleic acid and contrast agent carriers [3], or they may be used as antipathogenic compounds [4][5][6]. In vitro studies have revealed that these nanoparticles possess the ability to inhibit the fibrillation and aggregation of proteins involved in neurodegenerative disorders [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This character refers to end amine groups in dendrimer structure which interact with negative charge of membrane or cytoplasm microorganism causes bacterial cell wall damage and finally, inhabitation of bacterial activity (21). However, the PPI-G2 dendrimer is an efficient antibacterial agent against both Gram-negative and Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the end amino group in their structure is the cause of their microbicidal properties (20). Antimicrobial activity of dendrimers is related to some key factors such as dendrimer core type, dendrimer surface charge, their functional groups, dendrimer three-dimensional structure and its size (21). However, it is recognized that if site effects of dendrimers are cell walls or cell membranes, the anti-life stabilized on the dendrimers can be more effective (16).…”
Section: Introductionmentioning
confidence: 99%